When a Bilingual Child Describes Living Things: An Analysis of Conceptual Understandings from a Language Perspective. - Salleh, R.; Venville, G.; Treagust, David (Kluwer Academic Publishers, 2007)
With increasing numbers of students learning science through a second language in many school contexts, there is a need for research to focus on the impact language has on students’ understanding of science concepts. Like other countries, Brunei has adopted a bilingual system of education that incorporates two languages in imparting its curriculum. For the first three years of school, Brunei children are taught in Malay and then for the remainder of their education, instruction is in English. This research is concerned with the influence that this bilingual education system has on children’s learning of science. The purpose was to document the patterns of Brunei students’ developing understandings of the concepts of living and non-living things and examine the impact in the change in language as the medium of instruction. A cross-sectional case study design was used in one primary school. Data collection included an interview (n = 75), which consisted of forced-response and semi-structured interview questions, a categorisation task and classroom observation. Data were analysed quantitatively and qualitatively. The results indicate that the transition from Malay to English as the language of instruction from Primary 4 onwards restricted the students’ ability to express their understandings about living things, to discuss related scientific concepts and to interpret and analyse scientific questions. From a social constructivist perspective these language factors will potentially impact on the students’ cognitive development by limiting the expected growth of the students’ understandings of the concepts of living and non-living things.